2015
DOI: 10.1071/py13137
|View full text |Cite
|
Sign up to set email alerts
|

Importance of community engagement in primary health care: the case of Afghan refugees

Abstract: Refugees can experience problems accessing and utilising Australian primary health care services, resulting in suboptimal health outcomes. Little is known about the impact of their pre-migration health care experiences. This paper demonstrates how the Afghan pre-migration experiences of primary health care can affect engagement with Australian primary care services. It considers the implications for Australian primary health care policy, planning and delivery. This paper is based on the international experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Help‐seeking behaviours were also attributed to norms from participants' countries of origin, mirroring previous research concerning the knowledge, attitudes and practices of migrants towards oral health . Acculturation is a relatively novel addition to Andersen's Model relevant for this population and reflects previous research concerning the relevance of acculturation in promoting positive oral health beliefs and outcomes . Results also suggested combining oral health beliefs and behaviours (see also) to capture the interactions between beliefs—such as those associated with adherence to Islamic customs—and resulting oral health behaviours.…”
Section: Discussionsupporting
confidence: 75%
“…Help‐seeking behaviours were also attributed to norms from participants' countries of origin, mirroring previous research concerning the knowledge, attitudes and practices of migrants towards oral health . Acculturation is a relatively novel addition to Andersen's Model relevant for this population and reflects previous research concerning the relevance of acculturation in promoting positive oral health beliefs and outcomes . Results also suggested combining oral health beliefs and behaviours (see also) to capture the interactions between beliefs—such as those associated with adherence to Islamic customs—and resulting oral health behaviours.…”
Section: Discussionsupporting
confidence: 75%
“…For example, communication between health care service providers and patients is of key importance for building trust in health care institutions, where insufficient health literacy and language issues may specifically constitute important barriers in this regard [69]. Additional refugee-related factors such as socio-economic position in the host society, gender roles, lack of adequate information, difficulties in navigating organization of the health care services, and cultural beliefs and practices in regard to health and illness may potentially hamper access to health care utilization [57,65,69,70,71,72,73]. Engagement of the refugee communities in the development of health care policy and delivery, as well as participatory health care research, are suggested to be viable for addressing such barriers to care [69,71,72,74,75].…”
Section: Resultsmentioning
confidence: 99%
“…Publications in this area of action were conducted mainly between 2012 and 2018 (7/9) in Australia (2/9), the USA (2/9), Canada (2/9), and the Middle East (1/9) (+2/9 not specified), and populations addressed included refugees and asylum-seekers, immigrants of various descents, and vulnerable migrants [113][114][115][116][117][118][119][120][121]. Aspects of the interventions in primary healthcare discussed are engagement with the migrant community through partnerships [113,114], stronger focus on ancillary services [121], interdisciplinary collaboration between public health and primary care institutions [116][117][118], culturally and linguistically trained interpreters [118,119], evidence-based guidelines [118,119], outreach activities by nurses [120], training of staff in cultural competency [114,121], health promotion education among migrants, and advocacy [117,121].…”
Section: Primary Healthcarementioning
confidence: 99%